ANALISIS SENTIMEN PENDAPAT MASYARAKAT TERHADAP PPKM DKI JAKARTA DENGAN METODE NAÏVE BAYES - Hikari Ardhiansya (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
A virus called coronavirus, also known as COVID-19, can make people sick and even kill them. Several countries have been affected by the virus, including Indonesia, which has the COVID-19 virus. The Indonesian government has launched a number of strategies or efforts to prevent the long-term spread of COVID-19 in the country since the COVID-19 outbreak in Indonesia, such as imposing restrictions on community activities (PPKM). One of the areas conducting (PPKM), namely DKI Jakarta Province, which has the highest COVID distribution in Indonesia, So far, with the existence of restrictions on community activities in DKI Jakarta, the community has experienced difficulties carrying out their activities. Therefore, it is hoped that a sentiment analysis will look at people's opinions regarding PPKM in DKI Jakarta, which is currently starting to subside. The method to be used is Nave Bayes. A classification technique called Naive Bayes utilizes probabilistic and statistical techniques. The results of this sentiment analysis are 87.2% neutral, 4.3% positive, and 8.4% negative, and classification with Nave Bayes gives 2 classes 90% accuracy and 3 classes 81% accuracy. The dataset used is based on comments on YouTube in news content discussing PPKM DKI Jakarta. Sentiment analysis is generated using the following flow: cleaning, labeling, TF-IDF, splitting, classification, and evaluation. By using the Nave Bayes classification method, the researcher got the results for the Excellent classification category.